Increased inflammation with crude E. coli LPS protects against acute leptospirosis in hamsters. Issue 1 (1st January 2020) - Zhang, Wenlong; Xie, Xufeng; Wang, Jiaqi; Song, Ning; Lv, Tianbao; Wu, Dianjun; Zhang, Naisheng; Cao, Yongguo
ABSTRACT: Leptospirosis is a worldwide zoonotic disease that causes acute kidney injury, liver disease, bleeding disorders, and even death. Treatment of the disease is largely dependent on the use of antibiotics, but recent studies on pathogenesis of leptospirosis have shown that immunomodulation may also be an effective treatment for this disease. Since the delay in inflammation correlates with higher pathogenicity of leptospira, we studied the effect of inducing inflammation on leptospirosis by using TLR4 activator LPS. In accordance with our hypothesis, treatment with LPS protected against leptospirosis by enhancing the inflammatory response in hamsters. The gene expression levels of TLR2, TLR4, NLRP3 and inflammatory factors were higher in LPS-treated group during leptospira infection in hamsters. Although the levels of NO and iNOS were higher in LPS-treated group than in Leptospira-infected group, the protective effect induced by LPS is iNOS-independent. Treatment with LPS induced higher anti-leptospira IgG level than infection with leptospira alone. Then, expressions of costimulatory molecules and maturation markers were analysed. The data showed that treatment with LPS enhanced the expression of CD40, CD80 and CD86. Our results indicate that increased inflammation induced by LPS derived from Escherichia coli ( E. coli ) protects against leptospirosis in hamsters.